To eat or not to eat?: the curious affair of Western missionaries with Chinese food - Gibas, Piotr (Religio, 2023)
What did Western Christian missionaries eat in China and why, for the most part, was it not Chinese food? This study focuses on two groups of missionaries and their foodways - the Portuguese Jesuits (Catholics) based in Macau between the 16th and 17th centuries, and the British and American Protestants in Hong Kong and Shanghai in the 19th and early 20th centuries - and aims to reveal what they ate, what they refused to eat, and why. While examining ideological and cultural factors that modelled the diet of Christian missionaries, this study also analyzes Western ideas, perceptions, and phobias regarding Chinese food. While the Jesuits did have some religious concerns when approaching Chinese cuisine, they, for the most part, embraced it. The Protestants, on the other hand, who arrived much later and during the peak of Western domination in China, acted from a position of power and rejected local food on cultural and ideological grounds as inferior, unhygienic, and potentially poisonous. The early missionaries came to "sell" Christianity and were willing to negotiate their way with Chinese cuisine and culture, "christening" some aspects of them and adopting them as their own. In the age of imperialism, on the other hand, Christian missionaries intended to "civilize" the Chinese by imposing on them both their religious beliefs and their lifestyle, including their foodways.